Family Support in the Care of Patients with Type 2 Diabetes Mellitus: A Scoping Review - Setyoadi, Setyoadi; Mudianti, Jihan Faadhilah; Nifangelya, Prisilya; Ramadhania, Lailatul; Ismail, Dina Dewi Sartika Lestari (Journal of Nursing Science Update (JNSU), 2025)
The growing global incidence of Type 2 Diabetes Mellitus (T2DM) underscores the pressing need to investigate practical and sustainable management strategies. Type 2 diabetes mellitus (T2DM) is a chronic health condition that necessitates continuous monitoring and long-term care to maintain blood glucose levels within optimal limits. One critical factor influencing diabetes self-management is family support, which encompasses emotional, instrumental, informational, and appreciative dimensions. Family members play a crucial role in supporting individuals with T2DM by assisting with daily care routines, promoting adherence to treatment regimens, and offering motivation. This scoping review aims to critically evaluate the significance of family support as a key component in enhancing self-management among individuals diagnosed with type 2 diabetes mellitus (T2DM). It will outline the key elements of family support and investigate their relationship with diabetes-related outcomes, including glycemic control, medication adherence, and dietary adherence. The review encompasses an analysis of 15 pertinent articles retrieved from three key databases: ScienceDirect, Google Scholar, and ProQuest. The keywords employed comprised "family or caregiver support" and "diabetes mellitus type 2," integrated through the use of Boolean operators. The findings of this review indicate that family involvement considerably contributes to improved health outcomes for patients with T2DM. Individuals possessing robust family support demonstrate enhanced medication adherence, improved blood glucose levels, and greater compliance with dietary recommendations. In concludion, the integration of family support within diabetes management interventions has the potential to facilitate more effective and holistic approaches to treating type 2 diabetes mellitus (T2DM).